2005
DOI: 10.1002/cjoc.200591683
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mesomorphic Properties of 2-(4-Alkoxybenzoyloxy or 4-Alkoxycinnamoyloxy)-5-oxo-2,5-dihydrofurans

Abstract: Two series of p-alkoxybenzoates Ia-If and p-alkoxycinnamates IIa-IIf, each species bearing one terminal furanone, have been synthesized and characterized by IR, 13 C NMR, 1 H NMR, MS spectra and elemental analysis. The mesogenic properties of both series of furanones have been studied by polarizing optical microscopy and differential scanning calorimetry (DSC). The relationship between structures and mesogenic properties was discussed. The results show that the increased alkoxy chain length (C 7 -C 12 ) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…5-Acyloxy butenolides are readily synthesized in one step from the parent hydroxy butenolide HB , itself obtainable at a 100 gram-scale via continuous photooxygenation of furfural using our recently introduced photoflow reactor . Acylation of this cyclic hemiacetal with anhydrides or acyl chlorides , afforded esters 2 and carbonates 3 , whereas we found that the tin-catalyzed reaction with isocyanates produces carbamates 4 in high yields (Figure ). For the preparation of esters, Steglich esterification also proved to be highly suitable.…”
Section: Resultsmentioning
confidence: 88%
“…5-Acyloxy butenolides are readily synthesized in one step from the parent hydroxy butenolide HB , itself obtainable at a 100 gram-scale via continuous photooxygenation of furfural using our recently introduced photoflow reactor . Acylation of this cyclic hemiacetal with anhydrides or acyl chlorides , afforded esters 2 and carbonates 3 , whereas we found that the tin-catalyzed reaction with isocyanates produces carbamates 4 in high yields (Figure ). For the preparation of esters, Steglich esterification also proved to be highly suitable.…”
Section: Resultsmentioning
confidence: 88%
“…However, up to now, the use of DBD for gas phase epoxidation reaction has been rarely investigated. To our knowledge, only one recent published work described about gas phase epoxidation of propylene [31]; however, there has been no any literature reporting the epoxidation of ethylene using DBD yet.…”
Section: Introductionmentioning
confidence: 87%